Superior Fluorescent Nanoemulsion Illuminates Hepatocellular Carcinoma for Surgical Navigation - Zhu, Jing; Chu, Chengchao; Li, Dongsheng; Zhang, Yang; Cheng, Yi; Lin, Huirong; Wang, Xiaoyong; Liu, Junxian; Pang, Xin; Cheng, Jingliang; Liu, Gang (Frontiers in Bioengineering and Biotechnology, 2022)
Hepatocellular carcinoma (HCC), the fifth most common cancer worldwide, poses a severe threat to public health. Intraoperative fluorescence imaging provides a golden opportunity for surgeons to visualize tumor-involved margins, thereby implementing precise HCC resection with minimal damage to normal tissues. Here, a novel-acting contrast agent, which facilely bridges indocyanine green (ICG) and lipiodol using self-emulsifying nanotechnology, was developed for optical surgical navigation. Compared to clinically available ICG probe, our prepared nanoemulsion showed obviously red-shifted optical absorption and enhanced fluorescence intensity. Further benefiting from the shielding effect of lipiodol, the fluorescence stability and anti-photobleaching ability of nanoemulsion were highly improved, indicating a great capacity for long-lasting in vivo intraoperative imaging. Under the fluorescence guidance of nanoemulsion, the tumor tissues were clearly delineated with a signal-to-noise ratio above 5-fold, and then underwent a complete surgical resection from orthotopic HCC-bearing mice. Such superior fluorescence performances, ultrahigh tumor-to-liver contrast, as well as great bio-safety, warrants the great translational potential of nanoemulsion in precise HCC imaging and intraoperative navigation.